Animal Breed Composition Is Associated With the Hindgut Microbiota Structure and β-Lactam Resistance in the Multibreed Angus-Brahman Herd - Fan, Peixin; Nelson, Corwin D.; Driver, J. Danny; Elzo, Mauricio A.; Jeong, Kwangcheol Casey (Frontiers in Microbiology, 2019)
Antibiotics have been widely used in livestock to treat and prevent bacterial diseases. However, use of antibiotics has led to the emergence of antibiotic resistant microorganisms (ARMs) in food animals. Due to the decreased efficacy of antibiotics, alternatives to antibiotics that can reduce infectious diseases in food animals to enhance animal health and growth performance are urgently required. Here, we show that animal genetics is associated with the hindgut microbiome, which is related to fat deposition and beta-lactam resistance in the gastrointestinal tract. We investigated the hindgut microbiota structure in 95 postweaning heifers belonging to the unique multibreed Angus-Brahman herd with breed composition ranging from 100% Angus to 100% Brahman. The hindgut microbial composition of postweaning heifers differed among breed groups. The mucin-degrading bacterium Akkermansia known for promoting energy expenditure was enriched in Brahman calves that contained less intramuscular fat content, while butyrate-producing bacterium Faecalibacterium was linearly positively correlated with Angus proportion. Moreover, the higher relative abundance of beta-lactam resistant genes including ampC gene and arcA gene was associated with the greater Brahman proportion. As the first study aimed at understanding changes in hindgut microbiota among beef cattle with linear gradient of breed composition and its association with marbling in meat, our results suggest that the effects of animal genetics on the gut microbiota structure is associated with fat deposition and potentially a factor affecting the gut antimicrobial resistance.